استخدام المواد التعليمية العربية-الملايوية في تعلم النحو: دراسة حالة بجامعة ماكاسار الحكومية - سليمان, إسلامية; الخيرة, مفتاح; النساء, دينا مطيعة (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2023)
The significance of grammar within Arabic language proficiency remained incomplete in the Indonesian educational context, with challenges related to the utilization of Arabic educational materials. This research investigated the implementation and perception of Arabic education students at the State University of Makassar (UNM) concerning the adoption of Arabic-Malay educational materials in grammar instruction. Employing a case study method, data collection comprised two primary phases: interviews with 34 students from the 2022 cohort who had completed the first-semester grammar course and voluntarily engaged in unstructured interviews with the researcher, as well as the review of learning outcomes data and the content of educational materials. The collected data underwent analysis following the Miles and Huberman technique. The study's findings highlighted the positive impact of utilizing Arabic-Malay materials at UNM, as they facilitated grammar comprehension and enhanced student motivation. Nevertheless, some students required supplementary support. The success of learning was evidenced by the high academic performance of the students. علوم النحو لها دور أساسي في تكوين الكفاءة اللغوية العربية التي لم تكتمل بعد في التدريس في إندونيسيا، خاصة صعوبة استخدام المواد التعليمية باللغة العربية. لذلك، تهدف هذه الدراسة إلى تعميق تطبيق وإدراك طلاب تعليم اللغة العربية في جامعة ماكاسار الحكومية (UNM) بشأن استخدام المواد التعليمية العربية-الملايوية في تعلم النحو. استخدمت هذه الدراسة طريقة دراسة الحالة. تم جمع البيانات من خلال مرحلتين رئيسيتين، وهما مقابلات مع 34 طالبًا من دفعة 2022 الذين أكملوا مقرر النحو في الفصل الدراسي الأول ومستعدين لإجراء مقابلة غير منظمة مع الباحث والمستندات. أما المستندات فقد تم الحصول عليها من خلال مراجعة بيانات نتائج التعلم ومحتوى المواد التعليمية المستخدمة. ثم تم تحليل البيانات التي تم جمعها باستخدام تقنية تحليل البيانات Miles و Huberman. أظهرت نتائج الدراسة أن استخدام المواد العربية-الملايوية في UNM يوفر فوائد إيجابية، ويسهل فهم القواعد، ويزيد من دافعية الطلاب. ومع ذلك، يحتاج بعض الطلاب إلى دعم إضافي. يظهر نجاح التعلم من خلال درجات الطلاب العالية.